Support for SME international growth through green innovation subsidies : Case “Innovation support for growth companies” from the Recovery and Resilience Facility (RRF) subsidy instrument - Peltonen, Laura (My University, 2026)
Small and Medium-sized Enterprises (SMEs) play an essential role in national economies especially by providing innovation, growth and job creation therefore this study focuses on SMEs. One major challenge for SMEs is that they have to operate with limited resources. The lack of resources can act as a barrier for SMEs to undertake resource intensive activities such as innovation and internationalisation. Subsidies can act as a valuable external resource to assist firms to mitigate human, financial, marketing, informational, and allied resource constraints. Prior research indicates a positive interrelationship between innovation and internationalisation which is further explored in this study. This study focuses on the Recovery and Resilience Facility (RRF) which is a temporary monetary instrument by the European Commission. The case for this research is the RRF-subsidy “innovation support for growth companies” which was targeted to R&D projects of Finnish SMEs that promote sustainable development and are seeking growth through exporting. This study was conducted with a qualitative case study approach and representatives from five target SMEs were interviewed regarding their perceived benefits of this subsidy. The main research question for this study is: How does RRF-subsidy support green innovations, R&D, and international growth in SMEs? Subsidies play a key role in mitigating SME resource constraints by strengthening resources in SMEs. The RRF-subsidy strengthened resources and capabilities in SMEs therefore improving their capabilities to innovate and grow in international markets. Most of the target SMEs assessed that the RRF-subsidy advanced their substantive green innovations. Even though the RRF-subsidy was targeted to especially promote innovation activities, most of the target SMEs perceived that the subsidy advanced their international growth and competence to operate in international markets, thus supporting the use of innovation policy as an export policy and highlighting complementarity between innovation and internationalisation. The findings of this research give a comprehensive overview of how SMEs benefitted from this RRF-subsidy. Thus, the findings can be useful for SMEs that are planning to apply for similar subsidies. This study provides valuable insights for policymakers in the planning of future subsidy programs, ensuring that the subsidies more effectively address the needs of SMEs. These results and prior research emphasize that public subsidies should be allocated to SMEs.

Tutkimuksen kohteeksi valikoituivat pienet ja keskisuuret yritykset (pk-yritykset), koska niillä on kansantaloudessa merkittävä rooli innovaatioiden, kasvun ja uusien työpaikkojen luomisessa. Resurssiniukkuus vaikeuttaa huomattavasti pk-yrityksien toimintaa. Se voi estää pk-yrityksiä toteuttamasta resurssi-intensiivisiä toimia, kuten innovointia tai kansainvälistymistä. Tukien avulla pyritään poistamaan yritysten henkilöstö-, talous-, markkinointi-, informaatio- tai muita resurssirajoitteita. Aiempi tutkimus osoittaa positiivisen suhteen innovoinnin ja kansainvälistymisen välillä, mihin perehdytään tarkemmin tässä tutkimuksessa. Tämä tutkimus keskittyy elpymis- ja palautumistukivälineeseen (RRF), joka on Euroopan Komission väliaikainen taloudellinen tuki-instrumentti. Tutkimuksen kohteena on RRF-rahoitteinen Kasvuyrityksien innovaatiotuki. Tuki on kohdennettu suomalaisten pk-yrityksien TKI-projekteille, joilla edistetään kestävää kehitystä ja pyritään vientipohjaiseen kasvuun. Tutkimus toteutettiin kvalitatiivisena tapaustutkimuksena. Pk- yrityksistä haastateltiin viittä edustajaa saadun tuen koetuista hyödyistä. Päätutkimuskysymyksenä on: Miten RRF-tuki tukee vihreitä innovaatioita, tutkimus- ja kehitystoimintaa ja kansainvälistä kasvua pk-yrityksissä? Tuki-instrumentit ovat tärkeitä pk-yritysten resurssien vahvistamisessa. Tulokset osoittavat, että RRF-tuki vahvisti pk-yritysten resursseja ja valmiuksia ja siten paransi niiden kykyä innovoida ja kasvaa kansainvälisillä markkinoilla. Suurin osa kohde-pk-yrityksistä arvioi, että RRF-tuki edisti keskeisiä vihreitä innovaatiota. Vaikka RRF-tuki oli kohdennettu erityisesti innovaatiotoiminnan edistämiseen, suurin osa pk-yrityksistä koki, että tuki edisti niiden kansainvälistä kasvua ja kykyä toimia kansainvälisillä markkinoilla. Tämä tulos tukee innovaatiotukien hyödyntämistä vienninedistämisessä ja korostaa innovaatiotoiminnan ja kansainvälistymisen komplementaarisuutta. Tutkimuksen tulokset antavat kokonaisvaltaisen kuvan siitä, miten pk-yritykset hyötyivät RRF-tuesta. Tulokset voivat olla hyödyllisiä yrityksille, jotka aikovat hakea samankaltaisia tukia. Samalla tutkimus tarjoaa päättäjille arvokasta tietoa siitä, miten voidaan varmistaa, että tuet vastaavat jatkossa paremmin pk-yrityksien tarpeisiin. Saadut tulokset ja aiempi tutkimusnäyttö vahvistavat, että julkisia tukia tulisi jatkossa kohdentaa aiempaa enemmän pk-yrityksille.
Keywords: Subsidies; Public Subsidies; SMEs; Green innovation; R&D; Internationalisation; Yritystuet; Julkiset tuet; Pk-yritykset; Vihreä innovaatio; TKI; kansainvälistyminen